Correlation of body composition in early pregnancy on gestational diabetes mellitus under different body weights before pregnancy - Xintong, Li; Dongmei, Xu; Li, Zhang; Ruimin, Cao; Yide, Hao; Lingling, Cui; Tingting, Chen; Yingying, Guo; Jiaxin, Li (Frontiers in Endocrinology, 2022)
Objective: The prediction of gestational diabetes mellitus (GDM) by body composition-related indicators in the first trimester was analyzed under different body mass index (BMI) before pregnancy.Methods: Retrospective analysis of pregnant women who were treated, filed and regularly for perinatal care at the Third Affiliated Hospital of Zhengzhou University. They were single-born and had no diabetes before pregnancy. In the first trimester, the bioimpedance evaluation device was used to analyze body composition-related indicators such as protein, minerals, and waist-hip fat ratio. The Pearman correlation coefficient was used to evaluate the linear relationship between the continuous variable and pre-pregnancy body mass index (BMI). In the univariate body composition analysis, multivariate analysis was included for the risk associated with GDM, using the relative risk and 95% confidence interval obtained from logarithmic binomial regression, and generalized linear regression was used for multivariate regression analysis. Further, the area under the curve (AUC) is calculated by receiver operating characteristic (ROC). Results: In a retrospective study consisting of 6698 pregnant women, of which we collected 1109 cases of gestational diabetes. TBW, protein, minerals, BMC, BFM, SLM, FMM, SMM, BFP, WHR, VFL, and BMR, were higher in the GDM group than in the normal group and were statistically different (P<0.05). Among pregnant women with pre-pregnancy BMI ≥ 24kg/m2, before adjusting for confounding factors, body composition-related indicators were associated with the onset of GDM. In the primary data of pregnant women, the area under the receiver operating characteristic curve predicted by gestational weight gain to GDM was the largest (0.795), and its cutoff value was 1.415kg. In the results of body composition, the area under the receiver operating characteristic curve of body fat mass to predict GDM was larger (0.663) in all pregnant women. Conclusions: Through this retrospective study, it was found that body composition-related indicators were independently associated with the onset of GDM in both pre-pregnancy BMI < 24 kg/m2 and pre-pregnancy BMI≥24 kg/m2. In all pregnant women, the waist-hip ratio was found to be 4.562 times higher than the risk of GDM, and gestational weight gain was the best predictor of GDM.